1977
DOI: 10.1002/jez.1402020203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neurotransmitters upon the discharge of secretory product from the cutaneous glands of the red‐spotted newt

Abstract: The effects of sympathetic and parasympathetic agonists and antagonists on discharge of secretory product by the granular and mucous glands were examined in the red-spotted newt, Notopthalmus viridescens viridescens. Observations were made also on the South African clawed toad. Xenopus laevis, the grass frog, Rana pipiens, and the crested newt, Triturus cristatus. In contrast to the granular glands of the South African clawed toad and the grass frog, which were stimulated by alpha-adrenergic agents, those of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Since the smooth muscle cell layer is derived from the same layer as the myoepithelial cells surrounding the mucous and seromucous glands (see below), the question as to type of cell may not be significant. What seems clear is that, in the granular glands, these cells respond to a-adrenergic or nerve stimulation by contraction, and this results in the expulsion of the glandular contents (Hoffman and Dent, 1977;Benson and Hadley, 1969;Dockray and Hopkins, 1975). Since the granular glands do not show any ionic changes after a-adrenergic stimulation (Mills et al, unpublished observations), nor do they bind appreciable amounts of ouabain (Mills, 1984), the cells of the gland probably do not contribute to the ouabain-sensitive increase in short-circuit current and chloride transport elicited by exposure to isoproterenol Mills, 1981,1983).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Since the smooth muscle cell layer is derived from the same layer as the myoepithelial cells surrounding the mucous and seromucous glands (see below), the question as to type of cell may not be significant. What seems clear is that, in the granular glands, these cells respond to a-adrenergic or nerve stimulation by contraction, and this results in the expulsion of the glandular contents (Hoffman and Dent, 1977;Benson and Hadley, 1969;Dockray and Hopkins, 1975). Since the granular glands do not show any ionic changes after a-adrenergic stimulation (Mills et al, unpublished observations), nor do they bind appreciable amounts of ouabain (Mills, 1984), the cells of the gland probably do not contribute to the ouabain-sensitive increase in short-circuit current and chloride transport elicited by exposure to isoproterenol Mills, 1981,1983).…”
Section: Discussionmentioning
confidence: 97%
“…Electron microprobe analysis of ion shifts within the cells of the different glands of the frog skin indicates that during the initial stages of the shortcircuit current response only certain cell types respond to P-agonist stimulation (Mills et al, 1982a,b). Conversely, a-adrenergic stimulation appears to directly stimulate the smooth muscle or myoepithelial cells which surrdund the gland acini (Benson and Hadley, 1969;Hoffman and Dent, 1977). This astimulation results in secretion in bulk form by a rapid expulsion of material contained in the lumen of the gland with no change in transepithelial electrical characteristics (Watlington, 1968).…”
mentioning
confidence: 96%
“…At this moderate level of stimulation, the granular glands release significant quantities of material, but peptide stores are not fully depleted and are naturally replenished . Hoffman and Dent (1977) found that the granular glands of some urodeles discharged in response to acetylcholine rather than a-adrenergic agents. Sufficient peptides were collected from salamanders (Bolitoglossa) without injection.…”
Section: Collection Of Skin Peptidesmentioning
confidence: 99%
“…1). This initial secretion is probably due to the fact that PGE2 stimulate the smooth muscle or myoepithelial cells surrounding the gland acini (Benson & Hadley, 1969;Hoffman & Dent, 1977), a stimulation which results in a bulk secretion by a rapid expulsion of material contained in the lumen of the gland (Watlington, 1968). After the initial secretion pulse the glands of short-circuited skins bathed in C1-Ringer's solution continued to secrete, but not if the skins were bathed in NO3 Ringer's solution or in C1-Ringer's solution, in the presence of furosemide (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The initial secretion pulse involves a transient bulk expulsion of the contents of the acinus by contraction of smooth muscle or myoepithelial cells which surround the gland acini (Benson & Hadley, 1969;Hoffman & Dent, 1977). This expulsion is mediated via c~-adrenergic receptors and is not characterized by an increase in transepithelial current or ion transport (Watlington, 1968).…”
Section: Introductionmentioning
confidence: 99%